SOCIAL MEDIA AND TECHNOLOGY IN EDUCATION - Gulchehra Baxromova (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
Social media and modern technology have significantly transformed the way people communicate, learn, and interact with the world. These tools are now deeply integrated into education, daily life, and professional environments.Social platforms offer new ways of sharing knowledge, building communities,and encouraging creativity. However, they also raise concerns about mental health, privacy, and the quality of human interaction. This paper explores the impact of social media and technology, highlighting both benefits and challenges.